2000
DOI: 10.1051/aas:2000343
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of correlations between polarimetric and photometric characteristics of young stars

Abstract: Abstract. We present the results of the investigation of correlations between the polarimetric and photometric characteristics of a sample (496 objects) of young Herbig Ae/Be (HAEBE) stars and T Tauri (TT) stars. It is shown that, for 85% of the sample stars there is a general relation between the degree of optical polarization and the infrared colour index (V − L) obs and the colour excess E(V − L) due to the contribution of a circumstellar dust shell. Polarimetric data were also compared with the value of v … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 42 publications
(71 reference statements)
4
37
0
Order By: Relevance
“…This suggests the presence of a possible envelope as well as a circumstellar disk, or possibly a flared disk. The polarization is 4.7% (Yudin 2000).…”
Section: Eliasmentioning
confidence: 97%
“…This suggests the presence of a possible envelope as well as a circumstellar disk, or possibly a flared disk. The polarization is 4.7% (Yudin 2000).…”
Section: Eliasmentioning
confidence: 97%
“…Such a large NIR excess is often associated with polarised emission from the circumstellar matter (Yudin 2000), but Hales et al (2006) did not find any polarised emission and concluded that the disk may be too small to be resolved in their UKIRT observations. The decomposition of the N-band spectrum shows evidence of dust at a very early stage of processing.…”
Section: Hd 143 006mentioning
confidence: 99%
“…Menard Young stellar objects are also variable at X-ray, ultraviolet, infrared, and radio wavelengths. Each of these wavelength regimes probes a di †erent aspect of the young star and its circumstellar material, and they can be used together to establish a more comprehensive picture of the temporal properties and physical characteristics of young stellar objects (see, e.g., Kenyon et al 1994 ;Guenther et al 2000 ;Yudin 2000). Near-infrared monitoring observations, the focus of this study, are expected to probe relatively cool phenomena compared with optical, ultraviolet, and X-ray studies and may probe phenomena not accessible to shorter wavelength studies, such as temperature, opacity, and geometry changes in the dust-and gas-rich circumstellar environment.…”
Section: Introductionmentioning
confidence: 99%